2005
DOI: 10.1002/prot.20582
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium in the conformational dynamics and thermal stability of the D‐galactose/D‐glucose‐binding protein from Escherichia coli

Abstract: We have characterized stability and conformational dynamics of the calcium depleted D-galactose/D-glucose-binding protein (GGBP) from Escherichia coli. The structural stability of the protein was investigated by steady state and time resolved fluorescence, and far-UV circular dichroism in the temperature range from 20 degrees C to 70 degrees C. We have found that the absence of the Ca(2+) ion results in a significant destabilization of the C-terminal domain of the protein. In particular, the melting temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
3
29
0
Order By: Relevance
“…The smaller k q increase than the predicted one is a consequence of Trp shielding and a sign of dense residue packing. Similar behavior has previously been found for the glucose‐galactose binding protein in the presence of glucose 39. Quenching data indicate that at 90°C the TMBP structure partially opens, which results in a dramatic increase of the bimolecular quenching constant.…”
Section: Discussionsupporting
confidence: 81%
“…The smaller k q increase than the predicted one is a consequence of Trp shielding and a sign of dense residue packing. Similar behavior has previously been found for the glucose‐galactose binding protein in the presence of glucose 39. Quenching data indicate that at 90°C the TMBP structure partially opens, which results in a dramatic increase of the bimolecular quenching constant.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, it was also recently observed that the presence of Ca +2 in this protein enhances its thermal stability – neglecting this in our model could have an effect as well. [24] It is also possible that by adding additional chemistry to our coarse-grained model, such as Ramachandran potentials, hydrogen bonding, or residue-specific interactions, we might be able to observe a more realistic sampling of the fluctuations. We are currently working on such improvements.…”
Section: Discussionmentioning
confidence: 99%
“…The net of residues involved in the Ca 2ϩ coordination is not able to prevent calcium depletion. A previous work 29 showed that Ca 2ϩ depletion markedly reduces the thermal stability of the whole GGBP protein and especially the stability of the C-terminal domain. Although the metal ion is inserted in a binding site at the surface of the protein, it exerts a stabilizing effect that encompasses the whole structure of the protein.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Binding of glucose results in a minor 5% fluorescence quenching (data not shown), which is consistent with data published on the calcium depleted GGBP. 29 This quenching is probably the result of a stacking interaction between the pyranose ring of the bound sugar and the aromatic residues Phe 16 and Trp 183 of the protein. 13…”
Section: Spectral Propertiesmentioning
confidence: 99%